Influence of Perceived Value and Brand Awareness on Purchase Decisions for Volta Brand Electric Two-Wheeled Vehicles in Indonesia - Tri Nur Rohmawati; Paniya; Sri Wahyuni (JOBS (Jurnal Of Business Studies), 2025)
Volta is one of the most widely owned two-wheeled electric vehicle brands in Indonesia. However, electric motorcycle sales in Indonesia declined in early 2025 following a significant surge in 2023. This study aims to analyze the influence of perceived value and brand awareness on purchase decisions for Volta two-wheeled electric vehicle. A quantitative approach is employed, utilizing a survey method in which questionnaires are distributed to 97 Volta consumers across Indonesia to collect the necessary data. The data are analyzed using multiple linear regression with SPSS 23 software. The results indicate that both perceived value and brand awareness have a positive and significant effect on purchase decisions, both partially and simultaneously. This study is expected to contribute to the development of effective marketing strategies and help address the decline in two-wheeled electric vehicle sales in Indonesia.